(678) Economic Development التنمية الاقتصادية - Azizi, Alfonse (INP, 2024)
The key determinants of economic development in underdeveloped countries are the rate of investment and the mobilization of the potential economic surplus. There is also a debate on whether growth in these countries should be balanced or unbalanced. Underdeveloped countries face significant challenges in the process of industrialization, such as limited capital and technical skills, weak infrastructure, and high rates of unemployment and poverty. These countries also face important issues in the choice of appropriate techniques for economic development. Addressing these challenges requires comprehensive economic and development policies, including the mobilization of domestic resources, attracting foreign investment, developing infrastructure, improving education and training levels, and promoting innovation and appropriate technology. The success of economic development in underdeveloped countries requires strategic planning and coordination among various sectors and stakeholders to achieve sustainable growth and improve the living standards of the population.